Uma nova abordagem para o raciocinio não monotônico - Veras, Rodrigo de Melo Souza (2007)
Default logic was introduced to manipulate reasoning with incomplete information and became the main paradigm to formalize nonmonotonic reasoning. Many variations have been proposed with the objective to solve some limitations of the formalism or to consider different intuitions on the role of inconclusive information. However, some of the main characteristics had been kept: inconclusive information is represented as default rules, objectifies the calculation of extensions and, because this, they use characterizations through fixed-point operators. We consider a new approach for nonmonotonic reasoning. In this dissertation, we present the Defeasible Logic with Exception-First. The main advantages of this approach are: it does not use fixed-points operators to define expansions (our correspondent of extensions) and exception-first property that does not allow that a inconclusive proposition intervenes with the derivation of its exception. Moreover, we present a new way to define the extensions of default logic and two of its main variants, justified default logic and constrained default logic.